In whose name the Islamic world after 9/11 - Abbas (Thames & Hudson, 2009)
On 11 September 2001, the photographer Abbas watched the Twin Towers fall in New York - live on Siberian TV, thirteen time zones away. It spurred him to begin a journey through the Islamic world that would last seven years. The photographs published here are the final result of that project. Abbas is widely recognized as one of the most exceptional photographers of our time. These images represent some of the most memorable and compelling work he has produced.